Extension of measurement range of lubrication gap shape using vertical-objective-type ellipsometric microscopy with two compensator angles. (February 2020) - Namba, Katsuya; Fukuzawa, Kenji; Itoh, Shintaro; Zhang, Hedong; Azuma, Naoki
Abstract: A method for measuring gap shape during lubrication is presented that uses vertical-objective-type ellipsometric microscopy with two compensator angles. It extends the gap measurement range to over 200 nm and can provide measurement accuracy better than 2 nm for gaps of 0–200 nm without adding any special layer on the sliding surface. Furthermore, the proposed method successfully observed nanometric deformation of the sliding surface under reciprocating sliding conditions. The results suggested that lubrication gaps on the order of tens of nm did not obey conventional theory in the hydrodynamic lubrication regime. Highlights: A new gap-shape measurement method based on ellipsometric-microscopy was proposed. Addition of special layer to sliding surface is unnecessary to measure nm-order gap. Gap shape can be measured with accuracy better than 2 nm for gaps of 0–200 nm. Nanometric deformation of sliding surface due to lubricant flow was observed. Lubrication behavior in nm-order gaps did not obey conventional lubrication theory.